2002
DOI: 10.2105/ajph.92.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Problems With Access to Dental Care for Medicaid-Insured Children: What Caregivers Think

Abstract: Current proposals to solve the dental access problem probably will be insufficient until barriers identified by caregivers are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
148
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 13 publications
5
148
3
Order By: Relevance
“…Lack of transportation and limited appointment availabilities were reported by caregivers as 2 reasons they felt discouraged from seeking dental care for their children covered by Medicaid. 19 In addition, it has been reported that dental patients feel more comfortable with a provider of their own race. 19 This could have influenced minority utilization in our study, because Ͻ10% of the practicing dentists in NC represent minorities, 20 whereas ϳ38% of NC residents Յ5 years of age are of minority populations.…”
Section: Disparities In Dental Usementioning
confidence: 99%
“…Lack of transportation and limited appointment availabilities were reported by caregivers as 2 reasons they felt discouraged from seeking dental care for their children covered by Medicaid. 19 In addition, it has been reported that dental patients feel more comfortable with a provider of their own race. 19 This could have influenced minority utilization in our study, because Ͻ10% of the practicing dentists in NC represent minorities, 20 whereas ϳ38% of NC residents Յ5 years of age are of minority populations.…”
Section: Disparities In Dental Usementioning
confidence: 99%
“…However, the one woman who was adamant about how poorly she was treated by a Latina receptionist is a reminder that a health literate health organization is one that makes it easier for people to navigate and use information and services rather than creates barriers [16]. Perception of discrimination by parents whose child is covered by Medicaid is not unique to this study as others have documented similar problems [17,18]. These findings reinforce the importance of cultural competency training, communication skills and the need for health facilities to be 'user friendly. '…”
Section: Discussionmentioning
confidence: 84%
“…SCI patients are eligible for Medicaid, but it is difficult to find a dentist willing to take this form of payment. Moreover, patients perceive care as sub-standard when Medicaid is the source of payment [3] and only 50% of dentists report adequate financial compensation when Medicaid is the source of payment in treatment of the disabled population [36].…”
Section: Discussionmentioning
confidence: 99%
“…Among the services most difficult to access are dental services [2]. Obstacles that may limit maintenance of proper oral health include a lack of accessibility to the dental office [3], dental environment [3], lack of special needs dental professionals [4], poor quality of life, fear [5], lack of perceived need [6,7], and lack of financial assistance [8]. Dental offices are required to provide accessibility to the physically challenged and must follow the guidelines provided by the Americans with Disabilities Act (ADA) [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation